PENGGUNAAN DIALEK OSAKA DALAM KEHIDUPAN SEHARI-HARI –Studi Kasus Terhadap Mahasiswa Monbukagakushou Program Japanese Studies Tahun 2011– - Hidayat, Syafril Rahmad (Jurnal Ilmiah Mahasiswa FIB, 2013)
Dialect is one of language variations. Japan is the one of many countries in the world that has many variations of dialects. One of them is Osaka’s dialect. The writer chose Monbukagakushou Japanese Studies Program’s participants as the respondents because dialect is one of the culture that one country’s had and this program were teaching them about Japanese language and culture. There are two problems to be solved for the study, namely: (1) What vocabularies are usually used by the Monbukagakushou Japanese Studies program participants; and (2) What grammars are known by Monbukagakushou Japanese Studies program’s participants. This study is using quantitative description. The data source is questionnaires that were answered by 23 Monbukagakushou Japanese Studies Program’s participants. The results will be collected, tabulated, classified, then analyzed. As the results, there are 16 vocabularies were usually used by the respondents. Among those vocabularies, [Akan] is the most commonly used by the respondents. In the other hand, among 28 grammars were written in the questionnaire, 9 of them were known well by respondents. Among 9 grammars, 4 of them were known very well by the respondents. They are, [V~hen], [V~hin], [V~temoee], and [V~tara akan]. These words are known by 21 respondents (91,30%).   Key words : Monbukagakushou Japanese Studies, Osaka dialect, Case Study